Test Of The Effectiveness Of Root Alelopathic Extract (Cyperus rotundus L.) and Bandotan (Ageratum conyzoides L.) On The Growth Of Tomato Plants (Solanum lycopersicum L.) - Dewi Arini; Wahyu Harso; Asri Pirade Paserang (Biocelebes, 2019)
Cyperus rotundus L. and Ageratum conyzoides L. are commonly found in tomato field as weeds species. Weed compete with the crop for nutrient, water and light. In addition, weed released allelopathy that inhibited the growth of crop. The aim of this study was to compare the ability of allelopathy from C. rotundus L. and Ageratum conyzoides L. root extract to inhibit tomato plant growth. The study was conducted in Completey Randomized Design with two factors. The first factor was root extract from either C. rotundus L. and A. conyzoides L. as allelopathy. The second factor was concentration of root extract from both weeds (100, 300 and 500 g/ml). Each treatment combination was repeated four times. The results showed that A. conyzoides L. root extract had higher inhibition to growth of tomato plant than C. rotundus L. root extract. Increasing root extract concentration from both weeds increased inhibition of tomato plant growth.